The Functions of Cytochrome P450 ω-hydroxylases and the Associated Eicosanoids in Inflammation-Related Diseases - Ni, Kai-Di; Liu, Jun-Yan (Frontiers in Pharmacology, 2021)
The cytochrome P450 (CYP) omega hydroxylases, also known as CYP ꞷ-hydroxylases, are a group of subfamilies of CYPs. While CYPs are the main metabolic enzymes that mediate the oxidation reactions of many endogenous and exogenous chemicals in the human body, CYP ꞷ-hydroxylases mediate the metabolism of multiple fatty acids and their metabolites via the addition of a hydroxyl group to the ꞷ- or (ꞷ-1)-C atom of the substrates. The substrates of CYP ꞷ-hydroxylases include but not limiting to arachidonic acid, docosahexaenoic acid, eicosapentaenoic acid, epoxyeicosatrienoic acids, leukotrienes, and prostaglandins. The CYP ꞷ-hydroxylases-mediated metabolites, such as 20-hyroxyleicosatrienoic acid (20-HETE), 19-HETE, 20-hydroxyl leukotriene B4 (20-OH-LTB4), and many ꞷ-hydroxylated prostaglandins, have pleiotropic effects in inflammation and many inflammation-associated diseases. Here we reviewed the classification, tissue distribution of CYP ꞷ-hydroxylases and the role of their hydroxylated metabolites of arachidonic acid in inflammation-associated diseases. We found that up-regulation of CYP ꞷ-hydroxylases may be a pathogenic mechanism of many inflammation-associated diseases and thus CYP ꞷ-hydroxylases may be a therapeutic target for these diseases mainly accounting for the different effects of CYP ꞷ-hydroxylases-mediated eicosanoids. The roles of CYP ꞷ-hydroxylases-mediated eicosanoids in inflammation, acting as pro-inflammatory or anti-inflammatory mediators, involve in the process stimulated by cytokines and/or the process stimulating the production of multiple cytokines. However, most previous studies focused on 20-HETE. Therefore, further studies are needed for the function and mechanisms of other CYP ꞷ-hydroxylases-mediated eicosanoids. We believe that studies of CYP ꞷ-hydroxylases and their associated eicosanoids will advance the translational and clinal use of CYP ꞷ-hydroxylases inhibitors and activators in many diseases.